The role of mouthguards in the prevention of oro-facial trauma - Fine, P. D. (Research in Sports Medicine, 2025)
The role of a sports mouthguard has been well established as one of protecting teeth from trauma particularly during contact sports. The aim of this study is to review the roles of sports mouthguard at both an elite and recreational level. From the history of the first mouthguards, to a modern custom-made mouthguard, the role of the mouthguard has expanded. This review will look at the development of the mouthguard, the materials used to manufacture modern mouthguards and the different types available to elite and recreational athletes from a variety of sports. The mouthguard is now recognized as an essential piece of preventative equipment by many authors. This article shows that comfort, respiration and speech are not negatively affected by a well-fitting mouthguard. Many sports do not mandate the use of mouthguards but those that do have seen a significant reduction in oro-facial trauma incidence.